Bringing Indigenous Kamchatka to Google Earth: Collaborative Digital Mapping with the Itelmen Peoples - Thom, Brian; Colombi, Benedict J.; Degai, Tatiana (Sibirica, 2016)
Indigenous peoples in the Russian Far East are engaged in vibrant cultural and linguistic resurgence and revitalization through their community and regional organizations. Through the activities of one of these organizations, a computer-aided cultural mapping project was initiated in collaboration with indigenous villages along the Kamchatka Peninsula, working with youth and elders to map out the histories of special cultural places. The project utilized innovative participatory methodologies using Google Earth and related Google mapping tools, which are freely accessible and desired for use in the communities, providing an accessible, low-cost, easy-to-use computer application for detailed digital cultural mapping. This article elaborates on the use of these technologies to empower a community-based collaborative research project and reflects on critical issues in aligning community, corporate, and scholarly objectives in successful projects. This project is part of the Innovations in Ethnographic Mapping and Indigenous Cartographies project, funded by a Google Research Grant, and the Social Sciences and Humanities Research Council (SSHRC) Insight Development Grant, with additional funding from the National Science Foundation, the Arctic Social Sciences Program, and the US Fulbright Scholar Program. Faculty Reviewed 2018-12-15